A story about Creatinine Standardization! - Sheharbano Imran (Pakistan Journal of Kidney Diseases, 2021)
Today, serum creatinine (SCr) is still one of the most prescribed analyses in medical laboratories to estimate the glomerular filtration rate (GFR).Understanding by laboratories world-wide of the importance of reliable serum creatinine measurements in GFR estimation and of factors that may affect creatinine measurement is critical for the identification of patients with CKD. Serum creatinine assays must be properly calibrated and traceable to a high-order reference system in order to eliminate or significantly reduce variation among laboratories.